Prevalence of trachoma in indigenous and non-indigenous areas, Northeastern Brazil, 2019-2021 - Daniela Vaz Ferreira Gomez; Wanessa da Silva de Almeida; Paulo Roberto Borges de Souza Junior; Maria de Fátima Costa Lopes; Expedito José de Albuquerque Luna; Ivan Ricardo Zimmermann; Noemia Urruth Leão Tavares; Maria Margarita Urdaneta Gutierrez; Célia Landmann Szwarcwald (Pan American Health Organization, 2024)
Objective. To estimate the prevalence of trachoma in indigenous and non-indigenous populations in selected areas of the state of Maranhão, in northeastern Brazil. Methods. This was a population-based survey with probabilistic sampling. For the diagnosis of trachoma, external ocular examination was performed using head magnifying loupes, at 2.5X magnification. The prevalence of trachomatous inflammation - follicular (TF) in children aged 1-9 years and the prevalence of trachomatous trichiasis (TT) in the population aged ≥15 years were estimated. Relative frequencies of sociodemographic and environmental characteristics were obtained. Results. The study included 7 971 individuals, 3 429 from non-indigenous populations and 4 542 from indigenous populations. The prevalence of TF in non-indigenous and indigenous populations was 0.1% and 2.9%, respectively, and the prevalence of TT among indigenous populations was 0.1%. Conclusions. The prevalence of TF and TT in the two evaluation units in the state of Maranhão were within the limits recommended for the elimination of trachoma as a public health problem. However, the prevalence of TF was higher in the indigenous evaluation unit, indicating a greater vulnerability of this population to the disease. The prevalence of TF of below 5.0% implies a reduction in transmission, which may have resulted from improved socioeconomic conditions and/or the implementation of the World Health Organization SAFE strategy.